Assessment of genetic diversity and relatedness in the Latvian potato genetic resources collection by DArT genotyping. Issue 1 (14th August 2015) - Rungis, D. E.; Voronova, A.; Kokina, A.; Veinberga, I.; Skrabule, I.; Rostoks, N.
Abstract : Potato ( Solanum tuberosum L.) has been cultivated in Latvia since the 17th century, and formal breeding programmes have been established since the start of the 20th century. The Latvian potato genetic resource collection consists of 83 accessions of Latvian origin, including landraces, old cultivars released starting from the 1930's, modern cultivars and breeding material. These are maintained in field and in vitro collections. Pedigree information about the potato cultivars is often limited, and the use of hybrids of local cultivars as parents is common in the Latvian potato breeding programme. Ninety-four Latvian potato varieties and breeding lines and some commonly used foreign accessions were genotyped with the potato DNA diversity array technology. Analysis of the Latvian potato genetic resources collection revealed that the amount of genetic diversity has increased in the modern cultivars in comparison with the old cultivars.